We start by graphing the vertices of the triangle:
The first transformation is a translation 4 units to the right and 3 units up.
Then, we will get:
![\begin{gathered} A=(3,6)\longrightarrow A^(\prime)=(3+4,6+3)=(7,9) \\ B=(4,2)\longrightarrow B^(\prime)=(4+4,2+3)=(8,5) \\ C=(5,6)\longrightarrow C^(\prime)=(5+4,6+3)=(9,9) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d6ng7wbjs926tmbollkazcdd5e2o6toh25.png)
The rule applied for this translation is:
![(x,y)\longrightarrow(x+4,y+3)](https://img.qammunity.org/2023/formulas/mathematics/college/pl1spyxk0s9subnt3334tnkez9qd40njzv.png)
Now we have to reflect the points across the vertical line x=1. Only the horizontal coordinates will change, while the vertical coordinates remain equal.
This transformation has the rule:
![(x,y)\longrightarrow(2-x,y)](https://img.qammunity.org/2023/formulas/mathematics/college/jvss0aog1gq2w1q7jg16iio786njyp0j3o.png)
Then, we will have:
![\begin{gathered} A^(\prime)=(7,9)\longrightarrow A^(\prime)^(\prime)=(2-7,9)=(-5,9) \\ B^(\prime)=(8,5)\longrightarrow B^(\prime)^(\prime)=(2-8,5)=(-6,5) \\ C^(\prime)=(9,9)\longrightarrow C^(\prime)^(\prime)=(2-9,9)=(-7,9) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sb2ysmil20dqy09y6a67150x5oqt6zg6gp.png)
Now we can graph the image and the pre-image: